PHENOMENON OF DEBTOR FILING LAWSUIT AGAINST CREDITORS IN THE LOAN AGREEMENT WITH SECURITY RIGHTS AS A GUARANTEE - Ayu Kurniajati; ' Pranoto (Fakultas Hukum Universitas Sebelas Maret, 2021)
Abstract This article aims to assess on the reason for the debtor to sue creditor in a loan agreement and consideration of the judge in deciding the case. This writing uses legal research with statue approach and case approach. Based on research, several reasons for debtor to sue the creditor among others are default, tort, and debtor was not provided with sufficient time to read and understand the content of the loan agreement. The debtor in its lawsuit often provides statements that have actually not yet occurred. It can be said that the debtor is only making things up. On the other hand, the judge’s consideration of the debtor’s claim to the creditor is based on the reasons found on the court’s claim that is only to delay the execution time with respect to the auction of collateral.Abstrak Artikel ini bertujuan untuk mengkaji mengenai alasan debitur menggugat kreditur dalam perjanjian hutang piutang serta pertimbangan hakim dalam memutus perkara tersebut. Metode penulisan ini adalah legal research dengan pendekatan Perundang-undangan (statue approach) dan pendekatan kasus (case approach). Berdasarkan penelitian, beberapa alasan debitur kepada kreditur antara lain wanprestasi, perbuatan melawan hukum, serta debitur tidak diberikan waktu untuk membaca dan memahami isi perjanjian kredit. Debitur pada gugatannya seringkali memberikan pernyataan yang sebenarnya belum terjadi. Dapat dikatakan bahwa debitur hanya mengada- ada akan hal tersebut. Disisi lain, pertimbangan hakim mengenai gugatan debitur kepada kreditur yaitu berdasar alasan-alasan yang ditemukan di lapangan gugatan tersebut hanya untuk mengulur waktu eksekusi dalam pelelangan barang jaminan.